2013
DOI: 10.2174/2210289201304020043
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition and Antibacterial Activity of Neem (Azadirachta indica) Seed Oil

Abstract: Pneumonia and skin diseases are some types of severe infections occur worldwide due to pathogenic bacteria such as Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). These bacteria's do contribute towards other infections in human and thus lead towards unhealthy life. The aim of this study was to determine the fatty acid composition and to investigate the toxic effect of seed oil of Neem, genus Azadirachta of Azadirachta indica (Family: Meliaceae) against two multi-drug resistant bacteria, namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…Their lipid numbers have been further identified and their relative percentages recorded by mass spectrometry as shown in Table 1. These are mainly substituted and methylated octanoic and decanoic acids as also reported by other workers [18] . Undecanoic acid is an active ingredient of medications used in the treatment of Candida albicans skin infection [19] and has antiseborrheic property.…”
Section: Resultssupporting
confidence: 84%
“…Their lipid numbers have been further identified and their relative percentages recorded by mass spectrometry as shown in Table 1. These are mainly substituted and methylated octanoic and decanoic acids as also reported by other workers [18] . Undecanoic acid is an active ingredient of medications used in the treatment of Candida albicans skin infection [19] and has antiseborrheic property.…”
Section: Resultssupporting
confidence: 84%
“…Similar results were obtained by Akpuaka et al (2012) and Atabani et al (2013) who proved that neem oil has different fatty acids with different proportions and linoleic acid. Also, Sandanasamy et al (2013) demonstrated that linoleic acid is the main component in neem oil.…”
Section: Fig 1 Lc-p Line For Neem Oil and Cinnamic Oil Of Cowpea Apmentioning
confidence: 99%
“…By 2030 it is expected to increase to 7.7% and affecting 438 million adults. Between 2010 and 2030, there is an expected 69% increase in numbers of adults with diabetes in developing countries and a 20% increase in developed countries [5][6][7][8][9]. The agestandardized prevalence of diabetes in the rural and urban population ranged from 0.8% to 1.6% among adult Cameroonians.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) estimates that 80% of the worlds' populations uses traditional medicine. The continued use of traditional medicines is linked to their low cost and a general belief that they have minimal side effects [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation